THE INFLUENCE OF ADVERTISING VIEWS, ADVERTISING ATTRACTIVENESS, AND ADVERTISING POWER ON CAR PURCHASE DECISIONS IN THE COMMUNITY OF BANDAR LAMPUNG CITY - Febriansyah Febriansyah; Berlintina Permatasari (Universitas Nusa Cendana, 2026)
This study examines the influence of advertising exposure, advertising attractiveness, and advertising strength on consumers’ purchasing decisions. Drawing on advertising and consumer behavior perspectives, the research investigates how different dimensions of advertising effectiveness shape decision-making processes. The independent variables comprise advertising exposure, advertising attractiveness, and advertising strength, while purchasing decision serves as the dependent variable. Using a quantitative approach, data were collected through structured questionnaires administered to 400 respondents selected through probability sampling. The data were analyzed using multiple linear regression to assess both the individual and simultaneous effects of the proposed predictors on purchasing decisions. The findings indicate that advertising exposure, advertising attractiveness, and advertising strength each exert a significant positive influence on purchasing decisions. Furthermore, the three dimensions collectively contribute substantially to explaining variations in consumer purchasing behavior. These results highlight the importance of designing advertisements that are not only visible but also appealing and persuasive in order to enhance their impact on consumer decisions. The study contributes to the advertising literature by providing empirical evidence on the multidimensional role of advertising effectiveness in shaping purchasing behavior within a local urban context. However, as the research was conducted in Bandar Lampung City, the generalizability of the findings may be limited. Future research is encouraged to incorporate additional explanatory variables and extend the investigation to different geographical settings to strengthen the robustness and applicability of the results. Keywords: Ad Views; Ad Appeal; Ad Strength; Purchase Decision